The lion king (Bath, UK : Parragon Books, 2017)
"Young Simba wants to be a brave Lion King just like his father, Mufasa. But one day, Mufasa's cruel brother takes over the kingdom and Simba runs far away. When he grows up, Simba must choose his destiny - will he remain an outcast or claim his rightful place in the Circle of Life?"--Cover.
Keywords: Children's stories